Respostas

2014-08-02T14:15:39-03:00
f(x)=x^2-5x+6

 a - f(\sqrt{3})=(\sqrt{3})^2-5(\sqrt{3})+6
f(\sqrt{3})=3-5\sqrt{3}+6
f(\sqrt{3})=9-5\sqrt{3}
f(\sqrt{3})\approx9-5*1,732
f(\sqrt{3})\approx9-8,66
f(\sqrt{3})\approx0,34

b - f(x)=x^2-5x+6
f(x)=21
x^2-5x+6=21
x^2-5x+6-21=0
x^2-5x-15=0

x=\frac{-b\pm\sqrt{\Delta}}{2a}
x=\frac{-(-5)\pm\sqrt{\Delta}}{2*1}
x=\frac{5\pm\sqrt{\Delta}}{2}

\Delta=b^{2}-4ac
\Delta=(-5)^{2}-4*1*(-15)
\Delta=25+60
\Delta=85

x=\frac{5\pm\sqrt{85}}{2}
3 3 3
voce usou como formula de baskara eu preciso em forma de Função